The boy and the tigers - Bannerman, Helen; Petrone, Valeria (New York : Golden Books, 2004)
After giving four hungry tigers his beautiful new clothes so they won't eat him, Rajani finds them engaged in a fierce fight about who is the grandest, which proves to be their undoing.
Keywords: Boys -- India; Tigers; Pride and vanity; Boys; Pride and vanity; Boys; Pride and vanity; Tiger; India; India; India; Fiction; Juvenile works